REASONS FOR DIFFICULTY OF THE PHARMACOECONOMIC ANALYSIS FOR ORPHAN DRUGS. WAYS FOR SOLUTIONS - Andrey Vladislavovich Pavlysh; Aleksei Sergeevich Kolbin; Roman Andreevich Gapeshin; Stanislav Mikhailovich Malyshev (Фармакоэкономика)
Orphan drugs are used for treatment of rare life-threatening diseases. There is no universal definition of a rare disease and no universal approach to orphan drugs legislation. As a result, decision-making in this field requires results of pharmacoeconomic analysis, which structure and interpretation need a specific approach due to high costs of the drugs and limited sample size. Cost-utility analysis, risk management, and international rare diseases patient registries could be used to solve these problems.